Sextion: Sex Education for Civic Disposition (Sex Education as an Effort to Prevent Free Sex for College Students) - Aura Sabrina Malika; Laila Puspita Anggraeni; Nabila Rizkia; Nurul Sidiqah; Risca Dara Mutiara; Ahmad Fuadin (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
The rapid development of technology and information can affect adolescent behavior patterns, especially sexual behavior. The influence of social media is one of the causes of free sex behavior, easy access to videos with pornographic content and no supervision. Sex education should be obtained from the family, school and community. Sex education instills religion, character and norms in it so that children are always in accordance with religious teachings, norms and character demands as Indonesian citizens. With this understanding, they can be more careful in associating and dealing with the opposite sex. Sex education in civic education can be directed based on the social and moral components.